Analisis Tanggungjawab Pelaku Usaha Bisnis Kosmetik Terhadap Perbuatan Melawan Hukum Pengedaran Produk Skincare yang Terbukti Overclaim dengan Entitas Tanpa Izin Edar yang Jelas (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
This study aims to explore the practice of over-claiming in the skincare sector in Indonesia and its impact on consumers. With more and more products offering instant results in the absence of strong scientific evidence, consumers are often trapped in unrealistic expectations, which can jeopardise their health. The method used in this research is qualitative with a case study approach to analyse exaggerated claims as well as consumer reactions to certain skincare products. The findings of this study show that this practice harms consumers both materially and in terms of trust in the beauty industry as a whole. In addition, the results emphasise the importance of stricter law enforcement against offending businesses, including influencers who promote products with misleading information. In accordance with the Consumer Protection Law, consumers are entitled to clear and precise information, which is even more important in an era of aggressive marketing. Therefore, existing regulations, such as those issued by BPOM, need to be more strictly enforced to maintain the safety and effectiveness of the products being sold. The study also recommends raising awareness and educating consumers about the risks that may arise from overuse of skincare products. With these measures, it is hoped that the skincare industry can establish a more transparent and fair market, as well as improve product quality and protection for consumers. This research also contributes to a deeper understanding of the dynamics of the skincare market and the importance of consumer protection in legal and health aspects.